Trait personality in sport and exercise psychology: A mapping review and research agenda - Laborde, S.; Allen, M. S.; Katschak, K.; Mattonet, K.; Lachner, N. (International Journal of Sport and Exercise Psychology, 2020)
This study aimed to develop a systematic map of all trait-based research in sport and exercise psychology journals and to provide a detailed research agenda for progressing personality science in the context of sport and exercise. Abstracts were located for all articles published in 10 international journals from the field of sport and exercise psychology and were screened for trait measures. Definitions were obtained for each trait and thematic analysis was used to search for repeated patterns of meaning. We also mapped each trait to the 30 facets of the Big Five trait dimensions. Of the 5152 abstracts screened, 64 discrete traits were identified that met inclusion criteria. These traits could be categorised into 15 higher-order themes based on trait definitions. The most popular traits assessed in sport and exercise psychology research were trait anxiety, self-efficacy, perfectionism, social physique anxiety, and depression. The most popular higher-order themes were traits related to negative affect, self-confidence, perfectionism, competitiveness, and self-consciousness. Most traits could be mapped to facets of the Big Five, but some did not map well to any one particular facet. Few traits mapped to facets of agreeableness and openness. Eleven directions for future research are discussed including implications for systematic research synthesis.